GPRASP protein deficiency triggers lymphoproliferative disease by affecting B‐cell differentiation - Antonio Morales‐Hernández; Emilia Kooienga; Heather Sheppard; Gabriela Gheorghe; Claire Caprio; Ashley Chabot; Shannon McKinney‐Freeman (HemaSphere)
Abstract Gprasp1 and Gprasp2 encode proteins that control the stability and cellular trafficking of CXCR4, a master regulator of hematopoiesis whose dynamic regulation is required for appropriate trafficking of B‐cells in the germinal center (GC). Here, we report that Gprasp1 and Gprasp2‐deficient B‐cells accumulate in the GC and show transcriptional abnormalities, affecting the mechanisms controlling Aicda expression and exposing them to excessive somatic hypermutation. Consequently, about 30% of mice transplanted with Gprasp‐deficient hematopoietic stem and progenitor cells developed a biologically aggressive and fatal B‐cell hyperproliferative disease by 20–50 weeks posttransplant. Histological and molecular profiling reveal that Gprasp1‐ and Gprasp2‐deficient neoplasms morphologically resemble human high‐grade B‐cell lymphomas of germinal center origin with shared morphologic features of both Burkitt Lymphoma (BL) and diffuse large B‐cell lymphoma (DLBCL), and molecular features consistent with DLBCL, as well as elevated mutational burden and heterogenous transcriptional and mutational signature. Thus, reduced Gprasp1 and Gprasp2 gene expression perturbs B‐cell maturation and increases the risk of B‐cell neoplasms of germinal center origin. As this model recapitulates the essential features of the heterogenous group of human hematopoietic malignancies, it could be a powerful tool to interrogate the mechanisms of lymphomagenesis for these cancers.